2015
DOI: 10.1090/tran/6515
|View full text |Cite
|
Sign up to set email alerts
|

Uniform bounds for strongly 𝐹-regular surfaces

Abstract: Abstract. We show that if (X, B) is a two dimensional Kawamata log terminal pair defined over an algebraically closed field of characteristic p, and p is sufficiently large, depending only on the coefficients of B, then (X, B) is also strongly F -regular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…Let θ(X, B, M) be the number of those components of M which are not components of ⌊B⌋ (such θ functions were defined in 8.1 in a more general setting). By (7), S is not a component of ⌊B⌋, hence θ(X, B, M) > 0 otherwise K X + B is ample and R(K X + B) is finitely generated, a contradiction. Define…”
Section: 2mentioning
confidence: 97%
See 2 more Smart Citations
“…Let θ(X, B, M) be the number of those components of M which are not components of ⌊B⌋ (such θ functions were defined in 8.1 in a more general setting). By (7), S is not a component of ⌊B⌋, hence θ(X, B, M) > 0 otherwise K X + B is ample and R(K X + B) is finitely generated, a contradiction. Define…”
Section: 2mentioning
confidence: 97%
“…We will derive a contradiction. By replacing A with 1 m S where m is sufficiently divisible and S is a general member of |mA|, and changing M, B accordingly, we can assume that (7) S := Supp A is irreducible and K X + S + ∆ is ample for any boundary ∆ supported on Supp(B) − S.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…The proof is essentially the same as in the case where k is algebraically closed. When k is algebraically closed, the first assertion is nothing but [5,Theorem 4.1] and the second one follows from [31,Theorem 4.2]. Definition 5.4.…”
Section: Klt Singularitiesmentioning
confidence: 99%
“…Later on, the first author, together with Gongyo and Schwede, showed that a two-dimensional klt singularity (X, ∆) is strongly F -regular for big enough characteristic depending only on the coefficients of ∆ [CGS14].…”
Section: Introductionmentioning
confidence: 99%